Children exposure to indoor ultrafine particles in urban and rural school environments - Klara Slezakova (2016)
Extended exposure to ultrafine particles (UFPs) may lead to consequences in children due to their increased susceptibility when compared to older individuals. Since children spend in average 8 h/day in primary schools, assessing the number concentrations of UFPs in these institutions is important in order to evaluate the health risk for children in primary schools caused by indoor air pollution. Thus, the purpose of this study was to assess and determine the sources of indoor UFP number concentrations in urban and rural Portuguese primary schools. Indoor and outdoor ultrafine particle (UFP) number concentrations were measured in six urban schools (US) and two rural schools (RS) located in the north of Portugal, during the heating season. The mean number concentrations of indoor UFPs were significantly higher in urban schools than in rural ones (10.4 x 10(3) and 5.7 x 10(3) pt/cm(3), respectively). Higher UFP levels were associated with higher squared meters per student, floor levels closer to the ground, chalk boards, furniture or floor covering materials made of wood and windows with double-glazing. Indoor number concentrations of ultrafine-particles were inversely correlated with indoor CO2 levels. In the present work, indoor and outdoor concentrations of UFPs in public primary schools located in urban and rural areas were assessed, and the main sources were identified for each environment. The results not only showed that UFP pollution is present in augmented concentrations in US when compared to RS but also revealed some classroom/school characteristics that influence the concentrations of UFPs in primary schools.